Experimental Dramaturgy, Intellectual and Art-related Subjects in Irish Theatre - Kurdi, Mária (Hungarian Journal of English and American Studies, 2020)
Book review: Woodward, Guy, ed. Across the Boundaries: Talking about Thomas Kilroy. Dublin: Carysfort Press, 2014. 112 pages. ISBN 978-1-909325-51-7. Pbk. €25.00